Rethinking performance benchmarks in kidney transplantation. Issue 9 (12th June 2018) - Sheetz, Kyle H.; Englesbe, Michael J.
Abstract : This editorial discusses the implications of a recent study of kidney acceptance rates for programs undergoing a Systems Improvement Agreement by the Centers for Medicare and Medicaid Services. Seepage 2182 for the study from Bowring et al.